Expression, Characterization, and Evaluation of a RANK-binding Single Chain Fraction Variable: An Osteoclast Targeting Drug Delivery Strategy - Newa, M.; Lam, M.; Bhandari, K.; Xu, B.; Doschak, Michael (American Chemical Society, 2014)
A single chain Fraction variable (scFv) employs antibody-like target recognition specificity. Osteoclasts, responsible for bone resorption, express Receptor Activator of Nuclear factor Kappa B (RANK) receptors. This study aimed to express, characterize, and evaluate scFv against RANK receptors that may serve as a platform to target osteoclasts. Using phage display technology, scFv against RANK receptor was expressed and characterized by DNA sequencing, sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE), matrix-assisted laser desorption–ionization time-of-flight (MALDI TOF), enzyme-linked immunosorbent assay (ELISA), Western blot, and immunocytochemistry. The potential for cytotoxicity was evaluated using an MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide) assay, and its cross reactivity was evaluated using ELISA. Osteoclast-like cells were generated from RAW 264.7 cells, and the osteoclast targeting ability of scFv was evaluated using immunocytochemistry. ScFv’s antiresorptive efficacy was studied using a tartrate-resistant acid phosphatase (TRAP) assay and resorption assay. Anti-RANK scFv was successfully expressed and characterized. No cross reactivity with other tumor necrosis factor receptor (TNFR) members and no cytotoxic effect on a non-RANK bearing cell line were observed. It showed specificity toward a RANK receptor and an inhibitory effect on osteoclast activity. With the increase in development trends for biologics as therapeutics and growing knowledge on the importance of osteoclast targeted therapy, this study may provide a drug delivery strategy to target osteoclasts, thereby leading to a promising therapy for resorptive bone diseases.